MSDS software simplifies regulatory compliance. - Hicks, Lee (American City & County, 1998)
A material safety data sheet (MSDS) system was developed by officials in Denton, Texas, to standardize chemical storage data for city utilities to facilitate compliance with government MSDS regulations. The Denton system is based on the Comply Plus software from Dolphin Software, Lake Oswego, Oregon. The system is managed by one database administrator. Utility chemical data may be accessed by chemical or location.